PENGARUH PENGETAHUAN PERPAJAKAN DAN PENERAPAN E-FILINGTERHADAP KEPATUHAN WAJIB PAJAK DI KPP MAKASSAR UTARA - Dara Ayu Nianty (Bongaya Journal for Research in Accounting (BJRA), 2019)
The purpose of this study was to whether tax knowledge and application of efiling have an influence on taxpayer compliance in north Makassar tax office. Data obtained from 100 respondents registered as Taxpayers at the Makassar north Tax Office. Data collection is done through questionnaires. The data analysis technique used in this research is multiple linear regression. Based on the results of the analysis it can be seen that the tax knowledge and application of e-filing has a positive and significant effect of taxpayers compliance in northMakassar tax office.